Presentation of Financial Statements of a Non-Profit-Oriented Entity at Khalifah Kindergarten Pondok Kelapa Based on ISAK 35 - Veronica Indah Aprilia; I Gusti Ketut Agung Ulupui; Tri Hesti Utaminingtyas (PT. BATARI EDU CALYA, 2024)
This study aims to analyze the implementation of non-profit accounting at Khalifah Kindergarten Pondok Kelapa for the fiscal year 2022 and to examine the presentation of its financial statements in accordance with ISAK 35 (Interpretation of Financial Accounting Standards No. 35). The research employs Khalifah Kindergarten Pondok Kelapa as the object of study. A descriptive qualitative approach was adopted, utilizing both primary and secondary data. Data collection techniques included interviews and documentation. The findings indicate that the financial reporting practices of Khalifah Kindergarten Pondok Kelapa have not yet complied with ISAK 35. The institution’s reporting system is limited to recording cash receipts and cash disbursements. Based on documentation and interviews conducted with the administrative staff, it was found that the kindergarten has not prepared financial statements in accordance with the prescribed accounting standards for non-profit entities. Therefore, this study reconstructs and presents the financial statements in conformity with ISAK 35.